2021
DOI: 10.3847/1538-4357/abe4d2
|View full text |Cite
|
Sign up to set email alerts
|

Superposed Epoch Analysis of Galactic Cosmic Rays and Solar Wind based on ACE Observations During Two Recent Solar Minima

Abstract: Based on galactic cosmic ray (GCR) and plasma observations from the ACE spacecraft, in this work, we analyze the relation between the GCR counts and the solar wind parameters during two recent two solar minima (for the years 2007.0–2009.0, and 2016.5–2018.5) by means of the superposed epoch analysis (SEA) method. The results indicate that GCRs are strongly modulated by the co-rotating interaction regions (CIRs) in the solar wind, and that the occurrences of stream interfaces (SIs) between fast and slow solar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Guo et al. ( 2021a ) attempted to disentangle the drift and diffusive effects by performing SPE analyses with respect to both SI and SB crossings. They also studied a set of isolated HCS crossings without a nearby stream boundary.…”
Section: Galactic Cosmic Rays Perturbed By Transients In the Solar Windmentioning
confidence: 99%
“…Guo et al. ( 2021a ) attempted to disentangle the drift and diffusive effects by performing SPE analyses with respect to both SI and SB crossings. They also studied a set of isolated HCS crossings without a nearby stream boundary.…”
Section: Galactic Cosmic Rays Perturbed By Transients In the Solar Windmentioning
confidence: 99%
“…The results presented by Kirin et al (2020) show that a certain population of particles tends to stay bound to the shock for a certain period of time, indicating that this effect may explain the weak increase in GCR flux before the main FD decrease. Related to the compression in the frontal parts of CIRs, we also emphasize the so-called snowplow effect (e.g., Guo et al 2021), which is observed as the plasma density increase that starts even before the solar wind speed starts to rise, and which may also cause the GCR pre-CIR increase (Guo et al 2021).…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, a number of studies related to RFDs were published. For example, Kumar (2014), Badruddin & Kumar (2016), Ghanbari et al (2019), and Guo et al (2021) studied the behavior of RFDs by applying the superposed epoch analysis approach. We also refer to the observation-based studies by Modzelewska et al (2020) and Shen et al (2020), as well as to the numerical studies by Alania et al (2011), Guo & Florinski (2016), Kopp et al (2017), and Luo et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on a hybrid GCR transport model with a simulated CIR structure, Guo & Florinski (2014 investigated the relative roles of diffusion and drift processes. In addition to analyzing GCR and plasma observations from the ACE spacecraft, Guo et al (2021) found that drift effects seem to rival diffusion and convection at 1 au during the recent solar minimum periods. It is not clear whether this is applicable to all rigidities.…”
Section: Physical Processes and Cir Effectsmentioning
confidence: 99%